2022
DOI: 10.1039/d1tc04704c
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic electronic coupling/cross-talk between the isolated metal halide units of zero dimensional heterometallic (Sb, Mn) halide hybrid with enhanced emission

Abstract: Heterometallic 0D metal halide hybrids, consisting of more than one kind of metal halide units, are anticipated to manifest synergistic effects on the photo-physical properties of the constituent metal halide...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…For example, Biswas et al prepared zerodimensional tris SbMnCl crystals, in which the improved PLQY was due to the energy transfer from an SbCl 6 donor to a luminescent MnCl 6 acceptor. 27 The strategy also was utilized to design an all-inorganic Cs 4 MnBi 2 Cl 12 perovskite single crystal, profiting from the effective energy transfer from BiCl units to MnCl 6 , achieving 51-fold increments in PLQY compared with the monometal CsMnCl 3 •2H 2 O. 28 The synergistic effects show the huge potential to promote emission of Mn 2+ ions, but whether it works in CsMnBr 3 NCs remains to be verified.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…For example, Biswas et al prepared zerodimensional tris SbMnCl crystals, in which the improved PLQY was due to the energy transfer from an SbCl 6 donor to a luminescent MnCl 6 acceptor. 27 The strategy also was utilized to design an all-inorganic Cs 4 MnBi 2 Cl 12 perovskite single crystal, profiting from the effective energy transfer from BiCl units to MnCl 6 , achieving 51-fold increments in PLQY compared with the monometal CsMnCl 3 •2H 2 O. 28 The synergistic effects show the huge potential to promote emission of Mn 2+ ions, but whether it works in CsMnBr 3 NCs remains to be verified.…”
mentioning
confidence: 99%
“…Recently, it is reported that the synergistic effects between different metals can enhance the PLQY of heterometallic halide hybrids. , Heterometallic halide hybrids consist of more than one type of metal halide polyhedral units, thus making it possible to combine the PL features of different metal halide units. For example, Biswas et al prepared zero-dimensional tris SbMnCl crystals, in which the improved PLQY was due to the energy transfer from an SbCl 6 donor to a luminescent MnCl 6 acceptor .…”
mentioning
confidence: 99%
See 3 more Smart Citations